Fiscal autonomy of subnational governments and equity in healthcare resource allocation: Evidence from China - Yang, Ciran; Cui, Dan; Yin, Shicheng; Wu, Ruonan; Ke, Xinfeng; Liu, Xiaojun; Yang, Ying; Sun, Yixuan; Xu, Luxinyi; Teng, Caixia (Frontiers in Public Health, 2022)
Objectives: Promoting equity in healthcare resource allocation (EHRA) has become a critical political agenda of governments at all levels since the ambitious Universal Health Coverage was launched in China in 2009, while the role of an important institutional variable -- fiscal autonomy of subnational governments -- is often overlooked. The present study was designed to determine the effect of FASG on EHRA and its potential mechanism of action and heterogeneity characteristics to provide empirical support for the research field expansion and relative policies making of EHRA. Methods: From the start, we utilized the Theil index and the entropy method to calculate the EHRA index of 22 provinces (2011-2020) based on the medical resource data of 287 prefecture-level cities. Furthermore, we used the two-way fixed effects model (FE) to identify and analyze the impact of FASG on EHRA and then used three robustness test strategies and two-stage least squares (2SLS) regression to verify the reliability of the conclusions and deal with potential endogeneity problems respectively. At last, we run the threshold regression for heterogeneity analysis, which makes us verify whether the baseline model has nonlinear characteristics. Results: The static value and the trend of interannual changes in the EHRA values in different provinces are both very different. The regression results show that FASG has a significant positive impact on EHRA, and the corresponding estimated coefficient is -0.0849 (P < 0.01). Moreover, this promotion effect can be reflected through two channels: enhancing the intensity of government health expenditure (IGHE) and optimizing the allocation of human resources for health (AHRH). At last, under the different economic and demographic constraints, the impact of FASG on EHRA has nonlinear characteristics. Conclusions: FASG plays an essential role in promoting EHRA, which shows that subnational governments need to attach great importance to the construction of fiscal capability in the allocation of health care resources, effectively improve the equity of medical and health fiscal expenditures, and promote the sustainable improvement of the level of EHRA.